Suicidality and Associated Factors Among Men Who Have Sex With Men in Estonia. Issue 6 (12th May 2017) - Rüütel, Kristi; Valk, Anti; Lõhmus, Liilia
ABSTRACT: Many studies over the last decade provide strong evidence of elevated rates of suicidality among lesbian, gay, bisexual, and transgender populations compared to heterosexual populations. The aim of the current study was to investigate suicidal ideation and attempts and related factors among men who have sex with men (MSM) in Estonia. We conducted a nationwide Internet-based study among MSM with 265 eligible participants. Our results reveal high rates of self-reported suicidal ideation (lifetime prevalence 45%) and attempts (lifetime prevalence 11%) as well as a high rate of problem drinking (33%) and depressive symptoms (32%) among MSM. Recent suicidal ideation (14% had thought about suicide in the last 12 months) was related to depressive symptoms and lower socioeconomic situation. There is a need to develop specific interventions to address these issues among MSM and to provide gay-friendly mental health services.